Physicochemical homogeneity of stingless bee honey (Heterotrigona itama) produced in the west coast, east coast and inland area of Peninsular Malaysia - Ramlan, Nurul Ainaa Farhanah Mat; Mohamad Azman, Ezzat; Muhammad, Kharidah; Jusoh, Arif Zaidi; Johari, Nor Azfa; Yusof, Yus Aniza; Zawawi, Norhasnida (John Wiley and Sons, 2024)
BACKGROUND: The nutritional composition of stingless bee honey (SBH) can be affected by different climates and soil composition across different geographical areas. However, the range of attributes set for a honey quality standard should be inclusive. This study analysed the sugar profile's physiochemical properties, including quantifying the rare sugar trehalulose, organic acid and mineral composition of SBH collected from inland, and west and east coasts of Peninsular Malaysia. Forty-three SBH (Heterotrigona itama) samples were collected and labelled as <20 and <40 West Coast (<20WC, <40WC), <20 and <40 East Coast (<20EC, <40EC) and Inland, according to their distance from the coasts. RESULTS: The moisture, pH and sugar composition of all SBH samples adhered to the Malaysian Kelulut Honey Standard (MS2683:2017) but not to the International Codex Standard (CODEX) for honey. Trehalulose presence in all samples, regardless of geographical area, was predominant alongside fructose and glucose. Only hydroxymethylfurfural (HMF) content and electrical conductivity (EC) results complied with both standards. The principal component analysis biplot showed that the discrimination of SBH according to the five different areas was not feasible, indicating sample homogeneity. CONCLUSION: The physicochemical evaluation of SBH from Peninsular Malaysia shows mainly homogeneous attributes of samples across geographical locations. These findings demonstrated that the current MS2683:2017 is relevant and accommodates all SBH of H. itama species produced in Peninsular Malaysia. Furthermore, the trehalulose range calculated in this study can be implemented as a new benchmark for the indicator of SBH honey quality standard by national and international food standard committees.